2021
DOI: 10.1093/schbul/sbab064
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk Factor for Accelerated Brain Ageing in First-Episode Psychosis—A Longitudinal Study

Abstract: Background Obesity is highly prevalent in schizophrenia, with implications for psychiatric prognosis, possibly through links between obesity and brain structure. In this longitudinal study in first episode of psychosis (FEP), we used machine learning and structural magnetic resonance imaging (MRI) to study the impact of psychotic illness and obesity on brain ageing/neuroprogression shortly after illness onset. Methods We acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…The diffuse and uniform nature of the BMI‐related brain alterations may be more congruent with cortical thinning as a consequence of obesity. The negative effects of BMI on brain structure are supported by a Mendelian randomization study, 40 several longitudinal studies, demonstrating that obesity or obesity‐related metabolic alterations precede and accelerate brain changes over time 18,41 and by improvement of brain indices following a successful treatment of obesity 42–44 …”
Section: Discussionmentioning
confidence: 98%
“…The diffuse and uniform nature of the BMI‐related brain alterations may be more congruent with cortical thinning as a consequence of obesity. The negative effects of BMI on brain structure are supported by a Mendelian randomization study, 40 several longitudinal studies, demonstrating that obesity or obesity‐related metabolic alterations precede and accelerate brain changes over time 18,41 and by improvement of brain indices following a successful treatment of obesity 42–44 …”
Section: Discussionmentioning
confidence: 98%
“…41,42 In addition, obesity has also been found to increase risk of accelerated brain ageing in schizophrenia. 43 We found statistically significantly greater reductions in the metformin group than the placebo group for HbA1c and diastolic BP, although these reductions were not clinically meaningful. Previous studies of hypoglycaemic medications among people on clozapine have shown reductions in HbA1c 38,39 although it is possible that our findings may reflect a Type-I error associated with multiple analyses.…”
Section: Discussionmentioning
confidence: 55%
“…41,42 In addition, obesity has also been found to increase risk of accelerated brain ageing in schizophrenia. 43…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the current study does not inform on molecular changes that may underlie brain aging in schizophrenia. The available literature on brain aging suggests a potential role mainly for metabolic dysfunction ( 48 ) and low-level neuroinflammation ( 49 ) that should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%